2020
DOI: 10.26464/epp2020020
|View full text |Cite
|
Sign up to set email alerts
|

Gap formation around <em>Ω</em><sub>e</sub>/2 and generation of low-band whistler waves by Landau-resonant electrons in the magnetosphere: Predictions from dispersion theory

Abstract: In this paper we show that two significant phenomena of magnetospheric chorus emission can be explained by the participation of beam‐like electron structures, created by Landau‐resonant interaction with growing oblique whistler waves. The first concerns the widely observed spectral gap near half the electron cyclotron frequency Ω e; the second is related to the observation of very obliquely propagating lower‐band waves that cannot be directly generated by temperature anisotropy. Concerning the gap, kinetic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…Oblique whistler mode waves are damped by Landau‐resonant, suprathermal (20–1,000 eV) electrons, possessing a distribution with strong gradients in parallel velocities (see, e.g., Artemyev et al, 2016, and references therein). However, the presence of an additional field‐aligned electron population can significantly reduce this Landau damping and allow for oblique whistler mode wave generation (Gao et al, 2016; W. Li, Mourenas, et al, 2016; Mourenas et al, 2015; Sauer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oblique whistler mode waves are damped by Landau‐resonant, suprathermal (20–1,000 eV) electrons, possessing a distribution with strong gradients in parallel velocities (see, e.g., Artemyev et al, 2016, and references therein). However, the presence of an additional field‐aligned electron population can significantly reduce this Landau damping and allow for oblique whistler mode wave generation (Gao et al, 2016; W. Li, Mourenas, et al, 2016; Mourenas et al, 2015; Sauer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It depicts linear growth rate solutions for two cases, both including a primary distribution of transversely anisotropic electrons: Case F 0 does not include a field-aligned electron population, whereas case F 1 includes a low-density electron beam that forms a plateau in parallel velocities at ∼100-1,000 eV (note that there is no strong positive gradient with F 1 / v || > 0, but only F 1 / v || ≈ 0). The whistler mode wave growth rate calculated for distribution F 1 shows growth at large wave normal angles (very oblique whistler mode waves are generated near the resonance cone because of cyclotron instability and reduced Landau damping, see Mourenas et al, 2015;Sauer et al, 2020). Therefore, a realistic enhancement of the field-aligned electron population in the whistler mode wave source region can drive the generation of very oblique, quasielectrostatic whistler mode waves, which are indeed often observed in the inner magnetosphere (see statistics of such wave observations and their properties in Agapitov et al, 2013Agapitov et al, , 2018Gao et al, 2016;W.…”
Section: Whistler Mode Wave Growth Ratementioning
confidence: 99%
“…Based on a theoretical analysis, Sauer et al. (2020) have indicated that the plateau electrons can cause the damping around 0.5Ω e in whistler‐mode waves. Nevertheless, they haven't talked about how the plateau electrons are produced and how the energy is transferred around 0.5Ω e are still unknown.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Electromagnetic whistler waves, with frequencies between lower‐hybrid frequencies and electron cyclotron frequencies, are commonly observed in planetary magnetospheres and in the solar wind. These waves are driven by various types of electron anisotropy: thermal anisotropy (e.g., C. Kennel, 1966; Sagdeev & Shafranov, 1961), flow anisotropy (e.g., Sauer et al., 2020), or heat flux (Gary & Feldman, 1977; Tong et al., 2019; Vasko et al., 2020). This type of waves plays an important role in electron scattering and heating that are commonly described within the quasi‐linear approximation (C. F. Kennel & Engelmann, 1966; Trakhtengerts, 1966; Vedenov et al., 1962).…”
Section: Introductionmentioning
confidence: 99%